A heavy oil and residual oil hydrodemetallization catalyst and preparation method thereof
Through the design of multi-layer structure catalysts and multi-step impregnation process, the problem of insufficient activity and stability of hydrodemetalization catalysts in the prior art is solved, and efficient hydrodemetalization and demetalization reactions of heavy and residual oils are achieved, ensuring long-term operation stability and resistance to carbon deposits.
Patent Information
- Application Number
- CN202210458772.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-04-27
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2042-04-27
AI Technical Summary
The existing hydrodemetallic catalysts are insufficient in the hydrotreatment process of heavy and residual oil, making it difficult to meet the needs of long-term operation.
The catalyst design adopts a multi-layer structure, including the first alumina layer, the second alumina layer and the third alumina layer, forms a porous structure through multi-step aging and impregnation process, reasonably distributes the active metal components, and improves the catalyst's anti-packet Carbon properties and demetalization activity.
It significantly improves the activity and stability of the catalyst, ensures stable performance for long-term operation, and improves the utilization rate of active metals and the ability to resist carbon deposits.
Smart Images

Figure CN117000257B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a hydrodemetallization catalyst, in particular to a hydrodemetallization catalyst for heavy oil and residual oil hydrotreating process and a preparation method thereof. Background Art
[0002] In recent years, the trend of heavy and inferior crude oil has become increasingly serious, but the market demand for light oil products has continued to increase. This has caused the hydrogenation technology, which is an important treatment route for heavy oil, to face new challenges. As the core of hydrogenation technology, the preparation technology and performance of catalysts are of great significance for the deep hydrogenation of heavy oil. As for the hydrogenation of residual oil, the residual oil hydrodemetallization reaction is one of the important chemical reactions occurring during the residual oil hydroprocessing process. Under the action of the catalyst, various metal compounds react with H2S to generate metal sulfides, which are then deposited on the catalyst and removed. The existence state of active metals on the catalyst carrier is bound to play an important role in the activity and stability of the catalyst.
[0003] CN102441399A discloses a method for preparing a hydrodemetallization catalyst, wherein a metal compound of group VIB and / or a metal compound of group VIII is prepared into an ammonia solution or an aqueous solution, and then impregnated with an alumina carrier, and the final catalyst is obtained by drying and roasting. CN1289640A discloses a method for preparing a supported hydrodemetallization catalyst, wherein the method uses a macroporous alumina carrier, and an ammonia solution or an aqueous solution of an active metal is sprayed onto the carrier in a spraying drum, and the method omits the normal temperature drying process of the carrier after impregnation, and the sprayed carrier is directly placed in a roasting furnace at a temperature of 300 to 450°C for roasting, and then gradually heated to 460 to 550°C, and kept at a constant temperature for 1 to 5 hours under air conditions. CN103785400A discloses a method for preparing a highly active residual oil hydrodemetallization catalyst, wherein the method uses a polyol and / or monosaccharide aqueous solution to impregnate an alumina carrier, and after the impregnation, hydrothermal carbonization is performed in a sealed container, and then active metal components Mo and Ni are loaded on the carrier, and finally the alumina loaded with active components is first roasted in a nitrogen atmosphere, and then roasted in an air atmosphere to obtain a residual oil hydrodemetallization catalyst. CN111375419A discloses a hydrogenation catalyst and a method for preparing the same, wherein the method dissolves an iron-containing inorganic salt and an ammonium citrate salt in water to obtain a solution; the small-pore alumina is ball-formed, and the solution obtained in the first step is added at the same time to obtain alumina, the alumina is placed in a ball rolling machine, and macroporous alumina and the solution obtained in the first step are evenly added during the rolling process to obtain alumina again; the above-obtained alumina is dried to obtain the final alumina, and then the active metal components are loaded to obtain the catalyst.
[0004] The activity and stability of the hydrodemetallization catalyst prepared by the above method still need to be further improved. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention provides a heavy and residual oil hydrodemetallization catalyst and a preparation method thereof. When the catalyst is used for heavy and residual oil hydrodemetallization reaction, it has strong anti-carbon deposition performance, high demetallization activity and metal tolerance, and can ensure long-term operation of the device.
[0006] The first aspect of the present invention provides a heavy and residual oil hydrodemetallization catalyst, the catalyst comprising a catalyst intermediate and a second active component, the catalyst intermediate comprising a first alumina layer supporting the first active component and a catalyst inner layer consisting of a second alumina layer and a catalyst outer layer consisting of a third alumina layer; the mass ratio of the first active component in terms of oxide to the second active component in terms of oxide is 1.15 to 1.75, and in the catalyst, the ratio of the content of tetrahedral molybdenum to that of octahedral molybdenum in terms of Mo atoms is 0.16 to 0.32.
[0007] In the present invention, the heavy oil and residual oil hydrodemetallization catalyst is a spherical particle.
[0008] In the present invention, the diameter ratio of the second aluminum oxide layer to the first aluminum oxide layer is 2 to 9, preferably 2 to 5, and the diameter of the first aluminum oxide inner layer is 0.2 to 0.8 mm, preferably 0.4 to 0.6 mm.
[0009] In the present invention, the pore size of the first aluminum oxide layer is 8-18 nm, and the pore size of the second aluminum oxide layer is 16-28 nm. The pore size of the second aluminum oxide layer is 5-15 nm larger than the pore size of the first aluminum oxide inner layer.
[0010] In the present invention, the pore volume of the third alumina layer is 0.80 to 1.40 cm 3 / g, the pore volume with a pore diameter of 60-220 nm accounts for 25%-65% of the total pore volume.
[0011] In the present invention, the thickness of the third aluminum oxide layer is 100 to 480 μm, preferably 120 to 150 μm.
[0012] In the present invention, the first active component includes molybdenum and a Group VIII metal, and the Group VIII metal is preferably nickel; the second active component includes molybdenum and a Group VIII metal, and the Group VIII metal is preferably nickel.
[0013] In the present invention, based on the mass of the catalyst, the content of MoO3 is 9.0% to 20.0%, and the content of the Group VIII metal oxide is 2.0% to 12.0%.
[0014] In the present invention, the specific surface area of the catalyst is 150 to 200 m 2 / g, pore volume is 0.50-0.95mL / g; preferably, the specific surface area of the catalyst is 160-180m 2 / g, and the pore volume is 0.75~0.90mL / g.
[0015] In the present invention, the catalyst further comprises an auxiliary component, which is selected from at least one of fluorine, phosphorus, silicon or boron, preferably phosphorus. Based on the mass of the catalyst, the content of the auxiliary component in terms of oxide is 1.0% to 6.0%.
[0016] In the present invention, based on the mass of total molybdenum oxide in the catalyst, the content of molybdenum oxide in the first active metal component is 52% to 65%, and the content of molybdenum oxide in the second active metal component is 35% to 48%.
[0017] In the present invention, based on the mass of the total Group VIII metal oxide in the catalyst, the content of the Group VIII metal oxide in the first active metal component is 52% to 65%, and the content of the Group VIII metal oxide in the second active metal component is 35% to 48%.
[0018] The second aspect of the present invention provides a method for preparing the above-mentioned heavy oil and residual oil hydrodemetallization catalyst, the steps are as follows:
[0019] (1) neutralizing an acidic aluminum salt solution with an alkaline aluminum salt solution, and subjecting the solution to primary aging to obtain a slurry;
[0020] (2) the slurry obtained in step (1) is evenly divided into slurry I and slurry II, a water-soluble polymer J1 is added to slurry II, and slurry I and slurry II are subjected to secondary aging and drying, respectively, to obtain dried products I and dried products II;
[0021] (3) preparing a pseudo-boehmite mixed solution II by using the dried product II obtained in step (2) and adjusting its pH value, and sealing the mixture to obtain a mixed solution III;
[0022] (4) adding the dried product I obtained in step (2) and the mixed solution III obtained in step (3) to a rolling ball machine at a certain rate, and simultaneously spraying with a first impregnation solution containing a first active component at a uniform speed to obtain a first aluminum oxide layer;
[0023] (5) adjusting the relative dripping rate of the mixed solution III, continuing to spray the first impregnation solution containing the first active component at a uniform speed (to form a second alumina layer), drying, and calcining to obtain a catalyst inner layer;
[0024] (6) adding the catalyst inner layer obtained in step (5) into pseudo-boehmite gel, stirring and soaking, taking out after the surface is coated with gel (to form a third alumina layer), drying and calcining to obtain a catalyst intermediate;
[0025] (7) The catalyst intermediate obtained in step (6) is impregnated with a second impregnation solution containing a second active component in a saturated impregnation manner, and then dried and calcined to obtain the heavy and residual oil hydrodemetallization catalyst.
[0026] In step (1), the acidic aluminum salt solution and the alkaline aluminum salt solution are added to the reactor in a parallel flow.
[0027] In step (1), the acidic aluminum salt solution is one or more of aluminum sulfate solution, aluminum nitrate solution or aluminum chloride solution; the concentration of the acidic aluminum salt solution is 8g / 100mL to 45g / 100mL in terms of Al2O3. The alkaline aluminum salt solution is one or more of sodium metaaluminate solution and potassium metaaluminate solution; the concentration of the alkaline aluminum salt solution is 9g / 100mL to 55g / 100mL in terms of Al2O3.
[0028] In step (1), the neutralization reaction temperature is 80-140° C., the time is 30-160 min, and the pH value of the slurry is controlled to be 6.0-9.5 during the neutralization reaction. The pH value of the slurry is adjusted by controlling the addition rate of the acidic aluminum salt solution and the alkaline aluminum salt solution or by adding an additional acid-base regulator during the neutralization reaction.
[0029] In step (1), the primary aging temperature is 100-230° C., the time is 60-220 min, and the pH value is 9.0-12.0.
[0030] In step (1), after the primary aging is completed, preferably, the slurry is first concentrated and then subjected to secondary aging, wherein the volume of the concentrated slurry is 40% to 70% of the original volume.
[0031] In step (2), the water-soluble polymer J1 is one or more of polyethylene glycol, polyvinyl alcohol, polyacrylamide and methyl cellulose, preferably polyethylene glycol; the viscosity (20°C) of the water-soluble polymer J1 is 10 to 1000 mPa·s, and the viscosity (20°C) of the slurry after adding the water-soluble polymer J1 is 150 to 650 mPa·s.
[0032] In step (2), the secondary aging temperature is 120-260° C., the time is 40-200 min, and the secondary aging temperature is 30-60° C. higher than the primary aging temperature.
[0033] In step (2), the drying temperature after secondary aging is 120-180°C, the drying time is 2-10 hours, and filtering and washing can be performed according to conventional known methods before drying. The dry basis content of the dried product I and the dried product II obtained after drying is 40wt%-70wt%.
[0034] In step (3), the solid (mass) content of the obtained mixed solution III is 15% to 40%, the pH value ranges from 6.0 to 8.0, the adjustment method is solvent adjustment, the solvent can be one or more of phosphoric acid, nitric acid, oxalic acid, citric acid, and tartaric acid, and the sealing treatment time is 6 to 10 hours.
[0035] In step (4), the rotation speed of the ball rolling machine is 30-50 r / min. After the first ball forming is completed, the diameter of the obtained small balls is 0.2-0.8 mm.
[0036] In step (4), the addition rate ratio of the dried product I and the mixed solution III is 0.60-0.95 g / ml, the drop rate ratio of the first impregnation solution and the dried product I is 0.11-0.42 ml / g, and the drop addition time is based on the ball formation time.
[0037] In step (4), the amount of the first impregnation liquid accounts for 20% to 55% of the saturated water absorption of the dry substance I. The first impregnation liquid is an impregnation liquid containing Mo and a metal of Group VIII (preferably Ni), wherein the active metal component molybdenum is derived from one or both of molybdenum oxide and ammonium heptamolybdate, and the nickel is derived from one or both of basic nickel carbonate and nickel nitrate, and the contents of MoO3 and metal oxide of Group VIII in the first impregnation liquid are 20.0 to 50.0 g / 100 ml and 5.0 to 30.0 g / 100 ml, respectively. In step (4), at least one auxiliary agent containing fluorine, phosphorus, silicon or boron may also be introduced into the first impregnation liquid, and the amount of the auxiliary agent (in terms of oxide) added is 15% to 35% of the total mass of molybdenum oxide in the first impregnation liquid, preferably 18% to 28%.
[0038] In step (4), preferably, the first impregnation liquid further contains a water-soluble polymer J2. The water-soluble polymer J2 is one or more of polyethylene glycol, polyvinyl alcohol, polyacrylamide and methyl cellulose. The viscosity (20°C) of the water-soluble polymer J2 is 10 to 1000 mPa·s, and the viscosity (20°C) of the slurry after adding the water-soluble polymer J2 is 150 to 650 mPa·s.
[0039] In step (5), the ratio of the addition rate of the dried product I to the mixed solution III is 0.40 to 0.58 g / ml, and the ratio of the droplet addition rate of the first impregnation solution to the dried product I is 0.11 to 0.42 ml / g.
[0040] In step (5), the drying temperature is 120 to 200° C. and the drying time is 2 to 12 hours.
[0041] In step (5), the calcination is performed by programmed temperature increase, with a heating rate of 1°C / min to 3°C / min, a calcination temperature of 550°C to 750°C, a calcination time of 3 to 8 hours, and a calcination atmosphere of one or more of nitrogen, water vapor or air, preferably air.
[0042] In step (5), in the inner layer of the catalyst, the amount of MoO3 introduced into the catalyst by the first impregnation solution is 52% to 65% of the total MoO3 loading in the catalyst; the amount of Group VIII metal oxide introduced into the catalyst by the first impregnation solution is 52% to 65% of the total Group VIII metal oxide loading in the catalyst.
[0043] The concentration of alumina in the pseudo-boehmite gel in step (6) is 15 g / L to 60 g / L, preferably 18 g / L to 55 g / L. The pseudo-boehmite gel preferably contains one or more of fluorine, phosphorus, silicon or boron as an auxiliary agent; based on the mass of alumina, the amount of the auxiliary agent (in terms of element) added is 2.0% to 20% of the mass of alumina. Adding an auxiliary agent can change the surface structural properties of the alumina carrier, optimize the distribution form of the active metal in the secondary impregnation process, weaken the interaction between the active metal and the carrier, and further enhance the catalyst's ability to resist carbon deposition.
[0044] The pseudo-boehmite gel in step (6) can be obtained by the following method: using an inorganic aluminum source as a raw material, without adding a template, adjusting the pH value to 2.5-3.5, and performing a hydrothermal treatment at 140-260° C. for 2.0-10.0 h. The inorganic aluminum source can be selected from at least one of aluminum chloride, aluminum nitrate, and aluminum sulfate.
[0045] Before the inner layer of the catalyst is added to the macroporous pseudo-boehmite gel in step (6), the inner layer of the catalyst is preferably soaked in a binder solution. The mass content of the binder in the binder solution is 3% to 50%, preferably 3% to 25%. The binder solution is composed of a binder and pure water. The binder can be one or more of starch, dextrin, polyvinyl alcohol or carboxymethyl cellulose. Preferably, the inner layer of the catalyst is soaked in the binder solution for 0.5 to 5 minutes, excess binder solution is drained off, and the catalyst is left at room temperature for 20 to 60 minutes.
[0046] In step (6), the catalyst intermediate is added to the pseudo-boehmite gel and stirred for 0.5 to 20 minutes. After the surface is coated with gel, it is taken out and centrifuged to remove excess gel on the surface, and dried at 120 to 180° C. for 2 to 12 hours.
[0047] The calcination conditions in step (6) are: calcination at a temperature of 450-650°C for 3-6 hours to convert into a third alumina layer. The third alumina layer has the following properties: a pore volume of 0.80-1.40 cm 3 / g (mercury intrusion method), with open through pores, pores with a pore size of 60 to 220 nm occupy 25% to 65% of the total pore volume, and macromolecular reactants can be effectively diffused in the above-mentioned alumina layer.
[0048] The active metals in the second active metal impregnation solution in step (7) are preferably molybdenum and nickel. The content of MoO3 in the active metal impregnation solution is 5.0-20.0 g / 100 ml, and the content of NiO is 2.0-12.0 g / 100 ml.
[0049] The second impregnation solution in step (7) is an impregnation solution containing Mo and a Group VIII metal (preferably Ni), wherein the active metal component molybdenum is derived from one or both of molybdenum oxide and ammonium heptamolybdate, and nickel is derived from one or both of basic nickel carbonate and nickel nitrate. The amount of MoO3 introduced into the catalyst by the second impregnation solution is 35% to 48% of the total MoO3 loading in the catalyst; the amount of the Group VIII metal oxide introduced into the catalyst by the second impregnation solution is 35% to 48% of the total Group VIII metal oxide loading in the catalyst.
[0050] In step (7), preferably, the second impregnation liquid further contains a water-soluble polymer J3. The water-soluble polymer J3 is one or more of polyethylene glycol, polyvinyl alcohol, polyacrylamide and methyl cellulose. The viscosity (20°C) of the water-soluble polymer J3 is 10 to 1000 mPa·s, and the viscosity (20°C) of the slurry after adding the water-soluble polymer J3 is 150 to 650 mPa·s.
[0051] The impregnation method described in step (7) is saturated impregnation, the drying temperature is 120-200°C, and the drying time is 2-12 hours. The roasting method adopts programmed heating, the heating rate is 1°C / min-3°C / min, the roasting temperature is 400-550°C, and the roasting time is 3-6 hours.
[0052] Compared with the prior art, the present invention has the following beneficial effects:
[0053] The smooth pore structure and reasonable distribution of active metals are most important for the overall performance of the hydrodemetallization catalyst. For active metals, the reduction temperature of tetrahedral Mo species is greater than that of octahedral Mo species. The presence of tetrahedral Mo has an adverse effect on weakening the interaction between the carrier and the metal, thereby affecting the activity and stability of the catalyst. The inventors have found through extensive research that the slurry obtained after the neutralization reaction is first aged in two stages, and the slurry is not added or added with a water-soluble polymer before the secondary aging, and the secondary aging is performed at a higher temperature, so that porous materials with suitable specific surface areas and different pore size distributions, namely, dried products I and dried products II, can be obtained; the dried product II is formulated into a pseudo-boehmite mixed solution II, the pH is adjusted and sealed for a period of time to obtain a mixed solution III, and the dried product I and the mixed solution III are rolled into balls at a certain addition rate; during the ball forming process, the first impregnation liquid is sprayed therein at a uniform dripping rate. After the rolling ball grains grow to a certain size, the relative dripping rate of the mixed solution III is adjusted, and the first impregnation solution is continuously sprayed at a constant rate, and then after drying and calcination, a catalyst inner layer including a first aluminum oxide layer and a second aluminum oxide layer is obtained, and then a third aluminum oxide layer is coated on the surface of the catalyst inner layer, and the second impregnation solution is impregnated in a saturated impregnation manner, so that a third aluminum oxide layer containing a second active component can be formed on the surface of the catalyst inner layer to obtain the hydrogenation demetallization catalyst. The present invention introduces active metals in stages, so that the active metals are dispersed in a larger range in the catalyst inner layer, and the relative content of tetrahedral molybdenum and octahedral molybdenum in the final catalyst is effectively regulated; the third aluminum oxide layer coated on the outer surface of the catalyst inner layer makes the coke produced by thermal cracking of the residual oil first deposited in the third aluminum oxide layer on the surface, and the carbon deposition not only does not block the pores, but also can enter the interior of the catalyst for hydrogenation reaction, while improving the utilization rate of the active metal, but also improving the anti-coking performance of the catalyst. In summary, the method of the present invention achieves significant improvement in the activity and stability of the heavy and residual oil hydrodemetallization catalysts obtained through comprehensive coordination of various steps. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] Figure 1 This is a Raman spectrum of the catalyst surface obtained in Example 1;
[0055] Figure 2 This is a Raman spectrum of the catalyst surface obtained in Example 2;
[0056] Figure 3 This is a Raman spectrum of the catalyst surface obtained in Comparative Example 1;
[0057] Figure 4 This is the Raman spectrum of the catalyst surface obtained in Comparative Example 2. DETAILED DESCRIPTION
[0058] In the present invention, the Raman spectroscopic characterization of the catalyst was performed using a DXR Microscope type DXR micro Raman spectrometer from Thermo Scientific. -1 The peak nearby is the peak of tetrahedral molybdenum, at 960 cm -1 The nearby peak is the peak of octahedral molybdenum, and the contents of tetrahedral molybdenum and octahedral molybdenum are calculated based on the area under the same baseline.
[0059] In the present invention, the ASAP-2420 physical adsorption instrument of the Michael Company is used to characterize the pore structure (SVD) and specific surface area of the catalyst. The pore volume and pore diameter of the third alumina layer involved are obtained by mercury intrusion testing.
[0060] The technical solutions and effects of the present invention are further described below in conjunction with embodiments, but are not limited to the following embodiments.
[0061] Example 1
[0062] 1.5L of aluminum sulfate aqueous solution (the concentration of Al2O3 is 10.0g / 100mL, the initial temperature is 75°C) is introduced from the top into a reactor equipped with 5L of pure water, a stirrer and a heating jacket, and 1L of sodium aluminate aqueous solution (the concentration of Al2O3 is 28.0g / 100mL, the initial temperature is 110°C) is introduced from the bottom of the reactor, and the neutralization reaction temperature is controlled at 105°C; aluminum sulfate solution and sodium aluminate solution are added continuously, and the pH value is controlled to 8.5, and the reaction is carried out for 60 minutes; after the parallel flow is completed, an aging is carried out at a temperature of 150°C. , aging time is 120min, aging pH value is 9.3; after the first aging, the slurry volume is concentrated to 5L, and evenly divided into two parts, namely slurry I and slurry II, 25g of polyvinyl alcohol (viscosity is 30mPa·s) is added to slurry II, and the slurry viscosity (20℃) is 260mPa·s after adding polyvinyl alcohol, and slurry I is not treated in any way, then both slurry I and slurry II are heated to 180℃, and secondary aging is carried out, the aging time is 120min, and washed and dried to obtain dry matter I and dry matter II with a dry basis of 50wt% respectively;
[0063] The dried substance II and deionized water were mixed at a solid content of 16.7% to obtain a mixed solution II, and its pH value was adjusted to 6.5, and the mixture was sealed for 6 hours to obtain a mixed solution III. 800g of the dried substance I and 960ml of the mixed solution III were added to the ball rolling machine at an addition rate of 13.3g / min and 16.0ml / min, respectively, and the first impregnation liquid was sprayed at a drop rate of 2.0ml / min. The content of MoO3 in the first impregnation liquid was 28.3g / 100ml, the content of NiO was 4.7g / 100ml, the amount of P (in terms of oxide) in the auxiliary phosphoric acid was 24.1% of the total mass of molybdenum oxide in the impregnation liquid (the amount of the first impregnation liquid was 26% of the saturated water absorption of the dried substance I), and polyacrylamide (viscosity of 950mPa·s) was added to the first impregnation liquid, and the viscosity after addition was 600mPa·s, and the spraying time was controlled within 60min. The addition rate of the dried substance I was kept constant, and the dripping rate of the mixed solution III was changed to 24.0 ml / min. The first impregnation solution was continuously sprayed at a rate of 2.0 ml / min. The obtained sample was dried at 120°C for 6 hours and calcined at 750°C for 3 hours to obtain the inner layer of the hydrodemetallization catalyst. The amount of MoO3 introduced into the catalyst by the first impregnation solution was 54% of the total MoO3 loading in the catalyst; the amount of NiO introduced into the catalyst by the first impregnation solution was 54% of the total NiO loading in the catalyst.
[0064] Dissolve 65 grams of starch in 800 grams of pure water, heat and stir during mixing until the solid is evenly dissolved to obtain an adhesive solution. Weigh 42 grams of aluminum sulfate, add 3.6 grams of phosphoric acid, adjust the pH value to 3.5, and hydrothermally treat at 160°C for 3 hours, so that the concentration of alumina in the final pseudo-boehmite is 41g / L. Immerse the inner layer of the catalyst in the adhesive for 2.5 minutes, then take it out, wipe off the excess adhesive solution, and leave it at room temperature for 30 minutes. Finally, add the above sample to the pseudo-boehmite gel and stir for 15 minutes until the gel adheres to the surface and can be taken out, centrifuged in a high-speed centrifuge for 4 minutes, and then dried at 120°C for 6 hours. Then, calcine at 600°C for 3 hours to obtain a catalyst intermediate.
[0065] The second impregnation liquid is impregnated on the catalyst intermediate in a saturated impregnation manner, and polyacrylamide (viscosity of 950 mPa·s) is added to the second impregnation liquid, and the viscosity after addition is 400 mPa·s, wherein the amount of MoO3 introduced into the catalyst by the second impregnation liquid is 46% of the total MoO3 loading in the catalyst; the amount of NiO introduced into the catalyst by the second impregnation liquid is 46% of the total NiO loading in the catalyst, the spraying time is controlled within 60 minutes, and then dried at 120°C for 6 hours, and calcined at 450°C for 5 hours, wherein the heating rate of the calcination process is 3°C / min, to obtain the hydrodemetallization catalyst CAT-1.
[0066] The ratio of tetrahedral molybdenum to octahedral molybdenum in catalyst CAT-1 is 0.17. The thickness of the third alumina layer is 143 μm and the pore volume is 0.92 cm 3 / g, the pore volume with a pore size of 60-220 nm accounts for 36% of the total pore volume. Other physical and chemical properties of the catalyst are shown in Table 1.
[0067] Example 2
[0068] Compared with Example 1, the difference is that the initial temperature of the sodium aluminate aqueous solution added is 100°C, 50g of polyvinyl alcohol (viscosity of 30mPa·s) is added to the slurry II after the first aging, and the viscosity of the slurry after the addition of polyvinyl alcohol (20°C) is 280mPa·s;
[0069] The dried product II and deionized water were mixed at a solid content of 18.2% to obtain a mixed solution II, and the pH value thereof was adjusted to 7.0, and the mixture was sealed for 7 hours to obtain a mixed solution III. 800 g of the dried product I and 1040 ml of the mixed solution III were added to the ball rolling machine at addition rates of 13.3 g / min and 17.3 ml / min, respectively, and the first impregnation liquid (same as in Example 1) was sprayed therein at a drop rate of 2.0 ml / min, the addition rate of the dried product I was kept unchanged, and the drop rate of the mixed solution III was changed to 26.0 ml / min, and the first impregnation liquid was continued to be sprayed therein at a rate of 2.0 ml / min, and the obtained sample was dried at 120°C for 6 hours and calcined at 700°C for 4 hours to obtain the inner layer of the hydrogenation demetallization catalyst. The content of MoO3 in the first impregnation solution is 29.9g / 100ml, the content of NiO is 4.9g / 100ml, the amount of P (in terms of oxide) added in the auxiliary phosphoric acid is 24.1% of the total mass of molybdenum oxide in the impregnation solution (the amount of the first impregnation solution is 26% of the saturated water absorption of the dry substance I), and polyacrylamide (viscosity of 950mPa·s) is added to the first impregnation solution, and the viscosity after addition is 600mPa·s, wherein the amount of MoO3 introduced into the catalyst by the first impregnation solution is 57% of the total MoO3 loading in the catalyst; the amount of NiO introduced into the catalyst by the first impregnation solution is 57% of the total NiO loading in the catalyst.
[0070] Dissolve 65 grams of starch in 800 grams of pure water, heat and stir during mixing until the solid is evenly dissolved to obtain an adhesive solution. Weigh 42 grams of aluminum sulfate, add 3.6 grams of phosphoric acid, adjust the pH to 3.5, and hydrothermally treat at 160°C for 3 hours, so that the concentration of alumina in the final pseudo-boehmite is 37g / L. Immerse the inner layer of the catalyst in the adhesive for 2.0 minutes, then take it out, wipe off the excess adhesive solution, and leave it at room temperature for 20 minutes. Finally, add the above sample to the pseudo-boehmite gel and stir for 9 minutes until the gel adheres to the surface and can be taken out, centrifuged in a high-speed centrifuge for 5 minutes, and then dried at 140°C for 5 hours. Then, calcine at 550°C for 4 hours to obtain a catalyst intermediate.
[0071] During the calcination process after loading the second active metal, the temperature was raised to 500° C. at a heating rate of 3° C. / min and calcined for 4 h to obtain the hydrodemetallization catalyst CAT-2.
[0072] The ratio of tetrahedral molybdenum to octahedral molybdenum in catalyst CAT-2 is 0.21. The thickness of the third alumina layer is 137 μm and the pore volume is 0.89 cm 3 / g, and the pore volume with a pore size of 60-220 nm accounts for 34% of the total pore volume. Other physical and chemical properties of the catalyst are shown in Table 1.
[0073] Example 3
[0074] Compared with Example 1, the difference is that the dried product II and deionized water are mixed at a solid content of 20.0% to obtain a mixed solution II, and its pH value is adjusted to 7.5, and the mixture is sealed for 8 hours to obtain a mixed solution III. In the balling process, 800g of the dried product I and 1120ml of the mixed solution III are added to the ball rolling machine at an addition rate of 13.3g / min and 18.7ml / min, and the first impregnation liquid (same as Example 1) is sprayed therein at a dripping rate of 2.0ml / min. The dripping rate of the mixed solution III is adjusted to 28.0ml / min, and the first impregnation liquid is still sprayed therein at a rate of 2.0ml / min. The obtained sample is dried at 120°C for 6h and calcined at 650°C for 5h to obtain the inner layer of the hydrodemetallization catalyst. The content of MoO3 in the first impregnation solution is 31.4g / 100ml, the content of NiO is 5.2g / 100ml, the amount of P (in terms of oxide) added in the auxiliary phosphoric acid is 24.1% of the total mass of molybdenum oxide in the impregnation solution (the amount of the first impregnation solution is 26% of the saturated water absorption of the dry substance I), and polyacrylamide (viscosity of 950mPa·s) is added to the first impregnation solution, and the viscosity after addition is 600mPa·s, wherein the amount of MoO3 introduced into the catalyst by the first impregnation solution is 60% of the total MoO3 loading in the catalyst; the amount of NiO introduced into the catalyst by the first impregnation solution is 60% of the total NiO loading in the catalyst.
[0075] Dissolve 65 grams of starch in 800 grams of pure water, heat and stir during mixing until the solid is evenly dissolved to obtain an adhesive solution. Weigh 42 grams of aluminum sulfate, add 3.6 grams of phosphoric acid, adjust the pH value to 3.5, and hydrothermally treat at 160°C for 3 hours, so that the concentration of alumina in the final pseudo-boehmite is 33g / L. Immerse the inner layer of the catalyst in the adhesive for 1.5 minutes, then take it out, wipe off the excess adhesive solution, and leave it at room temperature for 20 minutes. Finally, add the above sample to the pseudo-boehmite gel and stir for 6 minutes until the gel adheres to the surface and then take it out, centrifuge it in a high-speed centrifuge for 6 minutes, and dry it at 160°C for 4 hours. Then, calcine at 500°C for 5 hours to obtain a catalyst intermediate.
[0076] During the calcination process after loading the second active metal, the temperature was raised to 550° C. at a heating rate of 3° C. / min and calcined for 3 h to obtain the hydrodemetallization catalyst CAT-3.
[0077] The ratio of tetrahedral molybdenum to octahedral molybdenum in catalyst CAT-3 is 0.26. The thickness of the third alumina layer is 131 μm and the pore volume is 0.87 cm 3 / g, the pore volume with a pore size of 60-220 nm accounts for 31% of the total pore volume. Other physical and chemical properties of the catalyst are shown in Table 1.
[0078] Example 4
[0079] Compared with Example 1, the difference is that the dried product II and deionized water are mixed at a solid content of 22.2% to obtain a mixed solution II, and its pH value is adjusted to 8.0, and the mixture is sealed for 9 hours to obtain a mixed solution III. In the ball forming process, 800g of the dried product I and 1200ml of the mixed solution II are added to the ball rolling machine at an addition rate of 13.3g / min and 20.0ml / min, and the first impregnation liquid (same as Example 1) is sprayed at a drip rate of 2.0ml / min. The drip rate of the mixed solution III is adjusted to 30.0ml / min, and the first impregnation liquid is still sprayed at a rate of 2.0ml / min. The obtained sample is dried at 120°C for 6h and calcined at 650°C for 5h to obtain the inner layer of the hydrodemetallization catalyst. The content of MoO3 in the first impregnation solution is 33.0g / 100ml, the content of NiO is 5.5g / 100ml, the amount of P (in terms of oxide) added in the auxiliary phosphoric acid is 24.1% of the total mass of molybdenum oxide in the impregnation solution (the amount of the first impregnation solution is 26% of the saturated water absorption of the dry substance I), and polyacrylamide (viscosity of 950mPa·s) is added to the first impregnation solution, and the viscosity after addition is 600mPa·s, wherein the amount of MoO3 introduced into the catalyst by the first impregnation solution is 63% of the total MoO3 loading in the catalyst; the amount of NiO introduced into the catalyst by the first impregnation solution is 63% of the total NiO loading in the catalyst.
[0080] Then 65 grams of starch was dissolved in 800 grams of pure water, and the mixture was heated and stirred until the solid was evenly dissolved to obtain a binder solution. 42 grams of aluminum sulfate was weighed, 3.6 grams of phosphoric acid was added, and the pH value was adjusted to 3.5. The mixture was hydrothermally treated at 160°C for 3 hours, so that the concentration of alumina in the final pseudo-boehmite was 29 g / L. The inner layer of the catalyst was immersed in the binder for 1.0 minutes, then taken out, the excess binder solution was wiped off, and placed at room temperature for 20 minutes. Finally, the above sample was added to the pseudo-boehmite gel and stirred for 4.5 minutes until the gel was attached to the surface and then taken out. After centrifugation in a high-speed centrifuge for 7 minutes, it was dried at 180°C for 3 hours. Then, it was calcined at 600°C for 6 hours to obtain a catalyst intermediate. During the calcination process after the second active metal was loaded, the temperature was raised to 600°C at a heating rate of 3°C / min and calcined for 6 hours to obtain a hydrodemetallization catalyst CAT-4.
[0081] The ratio of tetrahedral molybdenum to octahedral molybdenum in catalyst CAT-4 is 0.31. The thickness of the third alumina layer is 124 μm and the pore volume is 0.84 cm3 / g, and the pore volume with a pore size of 60-220 nm accounts for 29% of the total pore volume. Other physical and chemical properties of the catalyst are shown in Table 1.
[0082] Comparative Example 1
[0083] Compared with Example 1, the difference is that the slurry obtained after the first aging is directly heated, and then aged for the second time to obtain a dried product I; the dried product II is replaced by an equal amount of the dried product I for subsequent pelletizing process; and the hydrodemetallization catalyst dCAT-1 is prepared.
[0084] The ratio of tetrahedral molybdenum to octahedral molybdenum in catalyst dCAT-1 is 1.11. The thickness of the third alumina layer is 141 μm and the pore volume is 0.76 cm 3 / g, and the pore volume with a pore size of 60-220 nm accounts for 24% of the total pore volume. Other physical and chemical properties of the catalyst are shown in Table 1.
[0085] Comparative Example 2
[0086] Compared with Example 1, the difference is that during the ball forming process, the first and second impregnation liquids are not added, but after the ball forming is completed, the active metal loading process is carried out in a saturated impregnation manner to obtain a hydrodemetallization catalyst dCAT-2.
[0087] The ratio of tetrahedral molybdenum to octahedral molybdenum in catalyst dCAT-2 is 2.12. The thickness of the third alumina layer is 138 μm and the pore volume is 0.73 cm 3 / g, and the pore volume with a pore size of 60-220 nm accounts for 22% of the total pore volume. Other physical and chemical properties of the catalyst are shown in Table 1.
[0088] Comparative Example 3
[0089] Compared with Example 1, the difference is that during the whole ball forming process, the dry material I and the mixed liquid III are always added to the ball rolling machine at the addition rate of 13.3 g / min and 16.0 ml / min respectively; all the roasting processes are heated to 550°C at a heating rate of 3°C / min, and the roasting time is 3h. The hydrodemetallization catalyst dCAT-3 is obtained.
[0090] The ratio of tetrahedral molybdenum to octahedral molybdenum in catalyst dCAT-3 is 0.71. The thickness of the third alumina layer is 145 μm and the pore volume is 0.90 cm 3 / g, and the pore volume with a pore diameter of 60-220 nm accounts for 30% of the total pore volume. Other physical and chemical properties of the catalyst are shown in Table 1.
[0091] Comparative Example 4
[0092] Compared with Example 1, the difference is that the content of the first active component on the first alumina layer and the second alumina layer is 40% of the total active component content on the catalyst, and the content of the second active component on the third alumina layer is 60% of the total active component content on the catalyst; all calcination processes are heated to 550°C at a heating rate of 3°C / min, and the calcination time is 3h. Hydrodemetallization catalyst dCAT-4 is obtained.
[0093] The ratio of tetrahedral molybdenum to octahedral molybdenum in catalyst dCAT-4 is 1.73. The thickness of the third alumina layer is 141 μm and the pore volume is 0.81 cm 3 / g, and the pore volume with a pore diameter of 60-220 nm accounts for 25% of the total pore volume. Other physical and chemical properties of the catalyst are shown in Table 1.
[0094] Table 1 Physicochemical properties of various hydrodemetallization catalysts
[0095]
[0096]
[0097] Evaluation test
[0098] The activity stability test of Examples 1 to 4 and Comparative Examples 1 to 4 was carried out on a 200ml fixed bed hydrogenation test device. The raw oil was a residual oil raw material, the S content was 2.96wt%, the metal Ni and V contents were 33.4μg / g and 65.6μg / g respectively, the CCR content was 12.0wt%, and the demetallization rate of Example 1 when it was operated for 100h was 100%, and the others were relative demetallization rates. The specific test conditions are shown in Table 2, and the test results are shown in Table 3.
[0099] Table 2 Test conditions
[0100] Reaction temperature, °C 385 Reaction pressure, MPa 15.7 <![CDATA[Liquid hourly space velocity, h -1 > 1.0 Hydrogen to oil ratio, V / V 750
[0101] Table 3 Test results of various hydrodemetallization catalysts
[0102]
[0103]
[0104] It can be seen from Table 1, Table 2 and Table 3 that the hydrodemetallization catalyst prepared by the method of the present invention has a higher specific surface area and pore volume, and has higher reaction activity and stability, and can well meet the hydrodemetallization process of heavy and residual oils.
Claims
1. A heavy oil and residual oil hydrodemetallization catalyst, comprising a catalyst intermediate and a second active component, wherein the catalyst intermediate comprises a first alumina layer loaded with a first active component and a catalyst inner layer composed of a second alumina layer loaded with the first active component, and a catalyst outer layer composed of a third alumina layer; the mass ratio of the first active component in terms of oxide to the mass ratio of the second active component in terms of oxide is 1.15-1.75, and in the catalyst, the ratio of the content of tetrahedral molybdenum to that of octahedral molybdenum in terms of Mo atoms is 0.16-0.32; the catalyst is a spherical particle, the diameter ratio of the second alumina layer to the first alumina layer is 2-9, and the diameter of the first alumina layer is 0.2-0.8 mm; the pore size of the first alumina layer is 8-18 nm, and the pore size of the second alumina layer is 16-28 nm; wherein, The pore size of the second alumina layer is 5-15 nm larger than that of the first alumina layer; the pore volume of the third alumina layer is 0.80-1.40 cm 3 / g, the pore volume of pores with a pore diameter of 60-220 nm accounts for 25%-65% of the total pore volume, and the thickness of the third alumina layer is 100-480 μm.
2. The catalyst according to claim 1, characterized in that The diameter ratio of the second aluminum oxide layer to the first aluminum oxide layer is 2-5, and the diameter of the first aluminum oxide layer is 0.4-0.6 mm.
3. The catalyst according to claim 1, characterized in that The thickness of the third aluminum oxide layer is 120-150 μm.
4. The catalyst according to claim 1, characterized in that The first active component includes molybdenum and a Group VIII metal, and the second active component includes molybdenum and a Group VIII metal.
5. The catalyst according to claim 4, characterized in that The Group VIII metal in the first active component and the second active component is nickel.
6. The catalyst according to claim 4, characterized in that Based on the mass of the catalyst, the content of MoO3 is 9.0%~20.0%, and the content of the Group VIII metal oxide is 2.0%~12.0%.
7. The catalyst according to claim 4, characterized in that Based on the mass of total molybdenum oxide in the catalyst, the content of molybdenum oxide in the first active metal component is 52%~65%, and the content of molybdenum oxide in the second active metal component is 35%~48%; based on the mass of total Group VIII metal oxide in the catalyst, the content of Group VIII metal oxide in the first active metal component is 52%~65%, and the content of Group VIII metal oxide in the second active metal component is 35%~48%.
8. The catalyst according to claim 1, characterized in that The specific surface area of the catalyst is 150-200 m 2 / g, and the pore volume is 0.50~0.95mL / g.
9. The catalyst according to claim 1, characterized in that The specific surface area of the catalyst is 160-180 m 2 / g, and the pore volume is 0.75~0.90mL / g.
10. The catalyst according to claim 1, characterized in that The catalyst also includes an auxiliary component, which is selected from at least one of fluorine, phosphorus, silicon or boron. Based on the mass of the catalyst, the content of the auxiliary component in terms of oxide is 1.0% to 6.0%.
11. The catalyst according to claim 10, characterized in that The auxiliary component is phosphorus.
12. A method for preparing the catalyst according to any one of claims 1 to 9, comprising the steps of: (1) The acidic aluminum salt solution and the alkaline aluminum salt solution are subjected to a neutralization reaction and aged once to obtain a slurry; (2) the slurry obtained in step (1) is equally divided into slurry I and slurry II, a water-soluble polymer J1 is added to slurry II, slurry I and slurry II are subjected to secondary aging and drying, respectively, to obtain dried products I and dried products II; the water-soluble polymer J1 is one or more selected from the group consisting of polyethylene glycol, polyvinyl alcohol, polyacrylamide and methyl cellulose; (3) preparing a pseudo-boehmite mixed solution II with the dried product II obtained in step (2), adjusting its pH value, and sealing the mixture to obtain a mixed solution III; (4) adding the dried product I obtained in step (2) and the mixed solution III obtained in step (3) to a rolling ball machine at a certain rate, and simultaneously spraying with a first impregnation solution containing a first active component at a uniform rate to obtain a first aluminum oxide layer; (5) adjusting the relative dripping rate of the mixed solution III, continuing to spray the first impregnation solution containing the first active component at a uniform speed, drying, and calcining to obtain a catalyst inner layer; (6) adding the inner layer of the catalyst obtained in step (5) into the pseudo-boehmite gel, stirring and soaking, taking out after the surface is coated with the gel, drying and calcining to obtain a catalyst intermediate; (7) The catalyst intermediate obtained in step (6) is impregnated with a second impregnation solution containing a second active component in a saturated impregnation manner, and then dried and calcined to obtain the heavy and residual oil hydrodemetallization catalyst.
13. The preparation method according to claim 12, characterized in that: In step (1), the acidic aluminum salt solution and the alkaline aluminum salt solution are subjected to a parallel neutralization reaction; the concentration of the acidic aluminum salt solution in terms of Al2O3 is 8 g / 100 mL to 45 g / 100 mL; the concentration of the alkaline aluminum salt solution in terms of Al2O3 is 9 g / 100 mL to 55 g / 100 mL.
14. The preparation method according to claim 12, characterized in that: In step (1), the neutralization reaction temperature is 80-140° C., the time is 30-160 min, and the pH value of the slurry is controlled to be 6.0-9.5 during the neutralization reaction.
15. The preparation method according to claim 12, characterized in that: In step (1), the primary aging temperature is 100-230°C, the time is 60-220 min, and the pH value is 9.0-12.0; and / or, in step (2), the secondary aging temperature is 120-260°C, the time is 40-200 min, and the secondary aging temperature is 30-60°C higher than the primary aging temperature.
16. The preparation method according to claim 12, characterized in that: In step (2), the water-soluble polymer J1 is polyethylene glycol; the viscosity of the water-soluble polymer J1 at 20°C is 10-1000 mPa·s, and the viscosity of the slurry at 20°C after adding the water-soluble polymer J1 is 150-650 mPa·s.
17. The preparation method according to claim 12, characterized in that: In step (2), after the secondary aging, the drying temperature is 120-180° C., the drying time is 2-10 h, and the dry basis contents of the dried products I and II obtained after drying are both 40 wt %-70 wt %.
18. The preparation method according to claim 12, characterized in that: In step (3), the solid content of the obtained mixed solution III is 15% to 40%, the pH value is 6.0 to 8.0, and the sealing treatment time is 6 to 10 hours.
19. The preparation method according to claim 12, characterized in that: In step (4), the ratio of the addition rate of the dried substance I to the mixed solution III is 0.60-0.95 g / ml, and the ratio of the droplet rate of the first impregnating solution to the dried substance I is 0.11-0.42 ml / g; and / or, in step (5), the ratio of the addition rate of the dried substance I to the mixed solution III is 0.40-0.58 g / ml, and the ratio of the droplet rate of the first impregnating solution to the dried substance I is 0.11-0.42 ml / g.
20. The preparation method according to claim 12, characterized in that: In step (4), at least one auxiliary agent selected from the group consisting of fluorine, phosphorus, silicon and boron is introduced into the first impregnation solution, and the amount of the auxiliary agent added is 15% to 35% of the total mass of the molybdenum oxide in the first impregnation solution.
21. The preparation method according to claim 20, characterized in that: The amount of the additive added is 18% to 28% of the total mass of molybdenum oxide in the first impregnation solution.
22. The preparation method according to claim 12, characterized in that: In step (4), the amount of the first impregnation liquid used is 20% to 55% of the saturated water absorption of the dried material I.
23. The preparation method according to claim 12, characterized in that: In step (5), the calcination is carried out by programmed temperature rise, the temperature rise rate is 1°C / min~3°C / min, the calcination temperature is 450~750°C, the calcination time is 3~8h, and the calcination atmosphere is one or more of nitrogen, water vapor or air.
24. The preparation method according to claim 23, characterized in that: In step (5), the calcination atmosphere is air.
25. The preparation method according to claim 12, characterized in that: In step (6), the concentration of aluminum oxide in the pseudo-boehmite gel is 15 g / L to 60 g / L.
26. The preparation method according to claim 12, characterized in that: In step (6), the concentration of aluminum oxide in the pseudo-boehmite gel is 18 g / L to 55 g / L.
27. The preparation method according to claim 12, characterized in that: In step (6), the pseudo-boehmite gel contains one or more of fluorine, phosphorus, silicon or boron as an auxiliary agent; the amount of the auxiliary agent added in terms of element is 2.0% to 20% of the mass of the alumina, based on the mass of the alumina.
28. The preparation method according to claim 12, characterized in that: In step (6), before the catalyst inner layer is added to the pseudo-boehmite gel, the catalyst inner layer is soaked in a binder solution for 0.5 to 5 minutes, excess binder solution is drained off, and the catalyst is left at room temperature for 20 to 60 minutes.
29. The preparation method according to claim 28, characterized in that: The adhesive is one or more of starch, dextrin, polyvinyl alcohol or carboxymethyl cellulose, and the mass content of the adhesive in the adhesive solution is 3% to 50%.
30. The preparation method according to claim 28, characterized in that: The mass content of the adhesive in the adhesive solution is 3%~25%.
31. The preparation method according to claim 12, characterized in that: In step (6), the catalyst intermediate is added to the pseudo-boehmite gel and stirred for a soaking time of 0.5 to 20 minutes. After the surface is coated with gel, it is taken out and centrifuged to remove excess gel on the surface, and dried at 120 to 180° C. for 2 to 12 hours; and / or, in step (7), the calcination method adopts programmed heating, the heating rate is 1° C. / min to 3° C. / min, the calcination temperature is 400 to 550° C., and the calcination time is 3 to 6 hours.
Citation Information
Patent Citations
Method for preparing hydro-demetalization catalyst
CN102441399A
Preparation method of high-activity hydrodemetalization catalyst for residuum
CN103785400A
Hydrogenation catalyst and preparation method thereof
CN111375419A
Process for preparing carried catalyst for hydrogenation and demetalation
CN1289640A
Preparation method of hydrodemetalization catalyst for residuum
CN103785398A